Epidemiological and molecular identification of Trypanosoma vivax diagnosed in cattle during outbreaks in central Brazil - Bastos, Thiago Souza Azeredo; Faria, Adriana Marques; Couto, Luiz Fellipe Monteiro; Nicaretta, Joaõ Eduardo; Cavalcante, Alliny Souza De Assis; Zapa, Dina Maria Beltrán; Ferreira, Lorena Lopes; Heller, Luciana Maffini; Madrid, Darling Mélany De Carvalho; Cruvinel, Leonardo Bueno; Rossi, Gabriel Augusto Marques; Soares, Vando Edésio; et al. (Cambridge University Press (CUP), 2020)
Bovine trypanosomosis has been spreading in Brazil. In the present study, we evaluated the spatial distribution, prevalence and risk factors of this disease in the state of in Goiás, Brazil, and performed both molecular and phylogenetical analyses of Trypanosoma vivax. A total of 4,049 blood samples were collected from cattle for a period of two years. The parasitological diagnosis was performed using the Woo method and a questionnaire was administered to the farmers to document risk factors associated with the disease in the herd. Positive samples were DNA sequenced and compared to GenBank codes. The prevalence of T. vivax was 8.84%, occurring on 24 ranches only in dairy cattle and mainly in the central and southern portions of the state. The acquisition of new animals infected with T. vivax and the administration of exogenous oxytocin to cows using the same syringe and needle were the main associated factors (P ≤ 0.05). After an outbreak, milk production decreased by 39.62%. The presence of biting flies (tabanids, Haematobia irritans and Stomoxys calcitrans) were not a risk factor (P > 0.05) for the occurrence of T. vivax. The epidemiological data demonstrate the importance of restricting the practice of auctions as well as eliminating the use of exogenous oxytocin in animals during milking. The samples tested by PCR were positive for T. vivax and were genetically homologous with T. vivax found in different states of Brazil and west Africa based on the 18S rRNA gene.
Keywords: Biting flies; Epidemiology; Iatrogenic route; Molecular characterization; Risk factors; Trypanosomosis